2018
DOI: 10.1038/s41598-018-22921-6
|View full text |Cite
|
Sign up to set email alerts
|

Improving the surface properties of an UHMWPE shoulder implant with an atmospheric pressure plasma jet

Abstract: Insufficient glenoid fixation is one of the main reasons for failure in total shoulder arthroplasty. This is predominantly caused by the inert nature of the ultra-high molecular weight polyethylene (UHMWPE) used in the glenoid component of the implant, which makes it difficult to adhesively bind to bone cement or bone. Previous studies have shown that this adhesion can be ameliorated by changing the surface chemistry using plasma technology. An atmospheric pressure plasma jet is used to treat UHMWPE substrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 42 publications
3
43
0
Order By: Relevance
“…Furthermore, APP reactors do not require a vacuum atmosphere and special equipment. In spite of intensive studies, only a few groups have reported successful plasma polymerization using APP [15,16,17,18,19,20,21,22,23,24,25]. Our previous works recently reported the stationary APP jets (APPJs) polymerization employing the new types of impinging technique and ATP system [26,27,28,29,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, APP reactors do not require a vacuum atmosphere and special equipment. In spite of intensive studies, only a few groups have reported successful plasma polymerization using APP [15,16,17,18,19,20,21,22,23,24,25]. Our previous works recently reported the stationary APP jets (APPJs) polymerization employing the new types of impinging technique and ATP system [26,27,28,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, polymerized methyl methacrylate (polymethyl methacrylate, PMMA) having pinhole free characteristics has been widely used as organic thin films, encapsulations, biosensors, and electronics materials [21,22,23,24,25,31,32,33,34,35,36]. The plasma polymerizations of porous conducting polymers, such as aniline, pyrrole, and thiophene, have been successfully implemented using our APP polymerization technique [26,27,28,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Muzammil et al [ 9 ] used a pulsed plasma technique for the deposition of hydrophobic coatings on low-density polyethylene. Van Vrekhem et al [ 10 ] used an atmospheric pressure plasma jet for the treatment of ultrahigh-density polyethylene in order to improve the biological response of shoulder implants, and found improved adhesion to bone cement and an enhanced osteoblast proliferation. Lindner et al [ 11 ] used a high-impedance corona discharge in air for the treatment of various polymers and laminates, and the best results in terms of laminate bond strength were obtained for low-density polyethylene.…”
Section: Introductionmentioning
confidence: 99%
“…The study of noble gas flowing plasma has gained much attention in recent years due to its impact on the application of cold plasma jet and torches for soft ionization and mass spectrometry [1][2][3][4][5][6][7][8][9][10] .…”
mentioning
confidence: 99%